2022
DOI: 10.1111/ene.15652
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of language impairment in non‐demented amyotrophic lateral sclerosis patients

Abstract: Background and purpose This study aimed at estimating the prevalence of language impairment (LI) in a large, clinic‐based cohort of non‐demented amyotrophic lateral sclerosis (ALS) patients and assessing its underpinnings at motor and non‐motor levels. Methods Non‐demented ALS patients (N = 348) underwent the Edinburgh Cognitive and Behavioural ALS Screen (ECAS), as well as an assessment of behavioural/psychiatric and motor‐functional features. The prevalence of LI was estimated based on the proportion of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…When analyzing the results of the ECAS test in the participants, we observe that ALSFRS-R total score presents a low correlation with the ECAS sub-scores and total score, indicating that the same features used for detecting or monitoring ALS may not be helpful in inferring cognitive impairment. In fact, according to a recent study, the incidence of language impairment for non-demented people with ALS is estimated at 23% [28]. We also observe in Fig.…”
Section: Discussionsupporting
confidence: 70%
“…When analyzing the results of the ECAS test in the participants, we observe that ALSFRS-R total score presents a low correlation with the ECAS sub-scores and total score, indicating that the same features used for detecting or monitoring ALS may not be helpful in inferring cognitive impairment. In fact, according to a recent study, the incidence of language impairment for non-demented people with ALS is estimated at 23% [28]. We also observe in Fig.…”
Section: Discussionsupporting
confidence: 70%
“…the ECAS: although this test has been thoroughly shown to be clinimetrically sound and feasible within the Italian scenario [ 12 , 47 , 63 , 64 ], it is undoubtedly advisable that future studies further investigate the interplay between FTSDs and FI in this population by employing domain-/function-specific, second-level tests. Relatedly, it has to be mentioned that the ECAS-L has been criticized as not being able to fully cover the spectrum of ALS patients’ language phenotypes [ 45 , 62 , 63 ]: thus, future investigations should aim at replicating—or disconfirming—the present findings by employing a detailed and extensive set of second-level language measures. Finally, behavioural features were herewith assessed via both a caregiver-report—i.e.…”
Section: Discussionmentioning
confidence: 91%
“…The present study also sheds a light, for the first time, on the ecological relevance of LI in this population. LI within the spectrum of PPA [ 41 – 44 ] occurs in ≈23% of non-demented ALS patients [ 45 ], with its detection being also sufficient to classify patients as cognitively impaired according to Strong et al’s [ 1 ] revised criteria for FTSDs in ALS. Moreover, the incidence of LI in this population has been reported to increase over time [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, CLCC1related ALS patients in this study showed similar spinal onset as ALS patients reported by He et al Last, two patients in our study manifested cognitive decline mainly in language and executive domains, which are relatively vulnerable in ALS patients. 36,37 However, patients harboring CLCC1 variants also showed high heterogeneity clinically. The AAO of CLCC1 patients reported by He et al ranged from 17 to 74 years, and the survival time ranged from 38 to 135 months.…”
Section: Discussionmentioning
confidence: 99%
“…Last, two patients in our study manifested cognitive decline mainly in language and executive domains, which are relatively vulnerable in ALS patients. 36 , 37 However, patients harboring CLCC1 variants also showed high heterogeneity clinically. The AAO of CLCC1 patients reported by He et al.…”
Section: Discussionmentioning
confidence: 99%